Functional Network Changes After High-Frequency rTMS Over the Most Activated Speech-Related Area Combined With Speech Therapy in Chronic Stroke With Non-fluent Aphasia - Chang, Won Kee; Park, Jihong; Lee, Ji-Young; Cho, Sungmin; Lee, Jongseung; Kim, Won-Seok; Paik, Nam-Jong (Frontiers in Neurology, 2022)
Objective: High-frequency repetitive transcranial magnetic stimulation (HF-rTMS) to the lesional hemisphere requires prudence in selecting the appropriate stimulation spot. Functional near-infrared spectroscopy (fNIRS) can be used in both selecting the stimulation spot and assessing the changes of brain network. This study aimed to evaluate the effect of HF-rTMS on the most activated spot identified with fNIRS and assess the changes of brain functional network in the post-stroke aphasia patients. Methods: Five patients received HF-rTMS to the most activated area on the lesional hemisphere, followed by 30 minutes of speech therapy for 10 days. Korean Western aphasia battery (K-WAB) and fNIRS evaluation were done one day before the treatment, one day and one month after the last treatment session. Changes of K-WAB and paired cortical interaction and brain network analysis using graph theory were assessed. Results: Aphasia quotient in K-WAB significantly increased after the treatment (P=0.043). The correlation analysis of cortical interactions showed increased connectivity between language production and processing areas. Clustering coefficients of the left hemisphere were increased over a sparsity range between 0.45–0.58 (0.015 < p < 0.031), whereas the clustering coefficients of the right hemisphere, decreased over a sparsity range 0.15–0.87 (0.063 < p < 0.095). The global efficiency became lower over a network sparsity range between 0.47–0.75 (0.015 < p < 0.063). Conclusions: Improvement of language function and changes of cortico-cortical interaction between language-related cortical areas were observed after HF-rTMS on the most activated area identified by fNIRS with combined speech therapy in the post-stroke aphasia patients.